Political thought of the Third Position : Analysis in the context of Eternal Fascism according to Umberto Eco - Malendowicz, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The Third Position is one of the marginal currents in contemporary political thought. This current was represented by the International Third Position established in 1989. The values, concepts and arguments for the annihilation of parliamentary democracies and forms of contemporary international relations put forward by this organization raise the question: is the political thought of the Third Position (represented by the International Third Position) a fascist one? In the present article the author has formulated a hypothesis, according to which the political thought of the International Third Position is an ideology that meets the definition criteria of fascism. To verify it, the author used the theoretical framework presented in a lecture by the Italian writer and intellectual Umberto Eco (1932–2016) delivered in 1995 at Columbia University. The main method of verifying the hypothesis was a critical analysis of the elements of political thought of the International Third Position and comparing it with the features (symptoms) of fascism formulated by Eco. The source material for the analysis include documents of the International Third Position, as well as documents of political parties and organizations that make up the ITP from Italy and Poland. An important source were the ideological and journalistic texts written by the leaders of this movement from the UK, Poland and Italy. In the article, each of the fourteen features of fascism proposed by Umberto Eco was analyzed in the context of the thought of the Third Position. The research hypothesis has been positively verified. The political thought of the Third Position does indeed meet the defi nition criteria of fascism.
Keywords: Third Position; Eco, Umberto (1932–2016); fascism; far-right; political thought